2013
DOI: 10.1016/j.gaitpost.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Collision avoidance between two walkers: Role-dependent strategies

Abstract: This paper studies strategies for collision avoidance between two persons walking along crossing trajectories. It has been previously demonstrated that walkers are able to anticipate the risk of future collision and to react accordingly. The avoidance task has been described as a mutual control of the future distance of closest approach, MPD (i.e., Mininum Predicted Distance). In this paper, we studied the role of each walker in the task of controlling MPD. A specific question was: does the walker giving way (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(139 citation statements)
references
References 23 publications
12
119
1
Order By: Relevance
“…This effect of orientation on the clearance distance may be explained by the shape of the personal space, that was shown to be elliptic [6] with larger distance in the anteroposterior axis than the mediolateral one. In that sense, other authors attribute some role dependent strategies for collision avoidance between two walkers to the asymmetry of personal space [13]. This suggests that even in virtual conditions, users consider the personal space of the human obstacle in the collision avoidance task.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of orientation on the clearance distance may be explained by the shape of the personal space, that was shown to be elliptic [6] with larger distance in the anteroposterior axis than the mediolateral one. In that sense, other authors attribute some role dependent strategies for collision avoidance between two walkers to the asymmetry of personal space [13]. This suggests that even in virtual conditions, users consider the personal space of the human obstacle in the collision avoidance task.…”
Section: Discussionmentioning
confidence: 99%
“…Various groups of researches have studied human collision avoidance during walking [5,6,15,16,31,54,55,61]. They have been interested in when, where, as well as to which extent humans adjust their path or velocity to avoid a collision with another dynamic object.…”
Section: Related Workmentioning
confidence: 99%
“…A vital factor for achieving this goal is the awareness of the mutual influence between human individuals and the robotic systems. Modern robotic systems have to consider that humans are interaction-aware: they reason about the impact of possible future actions on the surrounding and expect similar anticipation from everyone else [6,55,61]. Of our particular interest is the interaction-aware navigation of humans, meaning the conditionally cooperative behavior that leads to mutual avoidance maneuvers.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, some interactions that pedestrians engage in are physical, but most are not. For example, physics approaches to treating streetscape dynamics may invoke considerations of distance and personal space in collision, which are relevant in examining Newtonian-type forces between pedestrians [88,91], whether through tangible collisions, or as human-perceived repulsion and attraction effects [73,[92][93][94][95][96]. However, decades of socio-behavioral science provide alternative cognitive and social explanations for much of the dynamics presented in physics-based models [45].…”
Section: Physicsmentioning
confidence: 99%
“…Reciprocity between potential colliders can also play a role in determining how, when, and by how much people will steer to avoid a collision [190]. Olivier et al [96] have shown that roles may be important in determining this over small bundles of space and time, and that these take on signaling schemes that intertwine with the positional data that are briefly exchanged and estimated as a person determines steering. Reciprocity may assume varying form, depending on different strategies, spacing, and timing when steering for animate and inanimate colliders [240].…”
Section: Steering To Avoid and Avail Of Interactionmentioning
confidence: 99%